Antibiotic resistant bacteria from sediment of coastal water of Pahang Malaysia - Ab Rahman, Nurhazlin; Chowdhury, Ahmed Jalal Khan; Zainal Abidin, Zaima Azira (2014)
This study was conducted to determine the presence of antibiotic resistance bacteria in sediment of coastal water of Pahang, Malaysia. A total of 64 bacteria were isolated and tested against 10 different antibiotics (Vancomycin, Tetracycline, Chloramphenicol, Streptomycin, Gentamycin, Penicillin G, Ampicillin, Erythromycin, Rifampicin and Polymyxin B). The greatest frequencies of resistance in bacteria were found in Polymyxin B (94%), Streptomycin (72%) and Penicillin G (50%) in Balok whilst, the high resistance of bacteria in Teluk Chempedak existed in Polymyxin B (100%), Erythromycin (63%) and Streptomycin (43%). Approximately 91% of Balok isolates and 87% of Teluk Chempedak isolates showed Multiple Antibiotic Resistance (MAR) index value higher than 0.2 (≥0.2) which suggest that there is a high-risk of antibiotics contamination in the area. Hence, findings from this preliminary study revealed the presence of antibiotic resistance bacterial strain in coastal water of Pahang, Malaysia and this may pose a potential public health hazard.